Income and Asset Disclosure: Case Study Illustrations - WorldBank (World Bank, 2015)
Income and asset disclosure systems (IAD) are gaining prominence as a tool in the fight against corruption, and have the potential to support efforts in both prevention and enforcement. They are intended to prevent and help detect the use of public office for private gain, and to help build a climate of integrity in public administration by detecting and helping officials avoid potential conflicts of interest. The potential for IAD systems to contribute to broader anticorruption efforts--such as national and international financial investigations and prosecutions, international asset recovery efforts, the prosecution of illicit enrichment, and the identification of politically exposed persons (PEPs) is as yet largely untapped.